Echocardiographic morphometry in healthy Bovine calves of upto 15 days of age - VERMA, ABHISHEK; SANGWAN, VANDANA; SINGH, NAVDEEP (The Indian Journal of Animal Sciences, 2025)
The present study was aimed to compare normal echocardiographic data in upto 15 days’ old cow and buffalo calves. The study included 26 healthy calves; 12 buffalo and 14 cow calves. The calves were clinically examined and auscultated for healthiness of chest and heart. Most of the calves included were females {64.28% (n=9) cow and 91.67% (n=11) buffalo calves}. Most of the buffalo calves were cross bred of Murrah, while the cow calves included Sahiwal (n=3), Rathi (n=1) and crossbreds of Holstein Friesian (n=9) and Jersey (n=1). The average body weight of buffalo calves (28.25 ± 6.59Kg) was non-significantly higher than the cow calves (25.57 ± 1.9Kg). The echocardiography was done from right side in both long and short axis. The various parameters recorded in right parasternal short axis view were; Interventricular septum thickness in systole and diastole, Left ventricular internal diameter in systole and diastole, Left ventricular posterior wall thickness in systole and diastole, Right ventricular internal diameter in diastole, End Point Septal Separation and Right atrial diastole diameter. The calculated parameters from short axis view included the fractional shortening and ejection fraction. The parameters recorded in right parasternal long axis view included; left atrium and aorta diameter in diastole and its ratio, the blood flow velocity at the aorta and mitral valve. A significantly higher left and right atrial diameter in diastole was recorded in buffalo calves in comparison to cow calves. However, the inter-ventricular wall thickness in diastole and the left ventricular posterior wall thickness in systole were significantly lower in buffalo calves in comparison to cow calves. The average left atrium to aorta ratio in diastole was 1.3 in both the species. The study concludes that a data base for echocardiographic morphometry was generated for upto 15 days old healthy bovine calves, which in future might help in the diagnosis of congenital heart defects in bovine calves. The study revealed statistically significant differences in the echocardiographic morphometry of cow and buffalo calves. The interventricular septum in diastole was observed to be thicker in cow calves, while the left ventricle posterior wall thickness in systole was greater in buffalo calves. Additionally, the diameters of the right and left ventricles and atrium were higher in buffalo calves compared to cow calves.